2021
DOI: 10.1039/d1nr02503a
|View full text |Cite
|
Sign up to set email alerts
|

Not all cells are created equal – endosomal escape in fluorescent nanodiamonds in different cells

Abstract: Successful delivery of fluorescent nanodiamonds (FNDs) into the cytoplasm is essential to many biological applications. Other applications require FNDs to stay within the endosomes. The diversity of cellular uptake of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 54 publications
(34 reference statements)
0
14
0
Order By: Relevance
“…This analysis clearly shows that some of the exposed cells had distinct response patterns while other cells had similar response patterns as control cells under all exposure conditions. One way to explain such distribution in the exposed cells is based on the previously reported heterogeneity of the NP load in individual cells, where some cells might carry no or only few NPs, while other cells can be loaded with hundreds or even thousands of NPs. Such a wide distribution in NP load per cell has been shown to correlate with a wide distribution in the level of responses.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This analysis clearly shows that some of the exposed cells had distinct response patterns while other cells had similar response patterns as control cells under all exposure conditions. One way to explain such distribution in the exposed cells is based on the previously reported heterogeneity of the NP load in individual cells, where some cells might carry no or only few NPs, while other cells can be loaded with hundreds or even thousands of NPs. Such a wide distribution in NP load per cell has been shown to correlate with a wide distribution in the level of responses.…”
Section: Resultsmentioning
confidence: 99%
“…The presence of multiple cell subpopulations is especially relevant to cells exposed to NPs. It has been shown that NP exposures end with a wide range of NP loads in individual cells, where some cells might carry no or only a few NPs, while other cells can be loaded with hundreds or even thousands of NPs per cell. Such wide distribution in NP load per cell has been shown to correlate with a wide distribution in the level of responses.…”
Section: Introductionmentioning
confidence: 99%
“…The time range from internalization until release of FNDs as well as if there is release or not varies greatly per cell type. 151 Recent studies showed that the shape and surface modification of FNDs can influence cellular uptake and endosomal escape. FNDs have been recognized in several studies as a safe and effective material which can escape the endosomes.…”
Section: ■ Labelingmentioning
confidence: 99%
“…To the best of our knowledge, there is a lack of systematic studies on endosomal escape of FNDs and dependence on the cell type and lifecycle stage. The time range from internalization until release of FNDs as well as if there is release or not varies greatly per cell type …”
Section: Labelingmentioning
confidence: 99%
“…To achieve cellular ingestion of NPs, surface modifications of the particles are often necessary. However, efficient uptake of non-functionalized NDs by various adherent cell cultures, especially HeLa cells, has been reported (4)(5)(6)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39). Despite their important role in inflammatory diseases and tumor progression, little research has been conducted studying NDs in phagocytic cells (27,(40)(41)(42).…”
Section: Introductionmentioning
confidence: 99%